THE ENGLISH IMMERSION PROGRAM: MEASURING THE COMMUNICATION OUTCOMES - Jane Lockwood (University of Kuningan, 2015)
This paper explores how language assessment is typically used to measure language gain as a result of the Immersion experience abroad. It also explores ways in which this might be improved. This study explores a recent experience where Australian immersion providers, participants and funders all report significant intercultural awareness raising and improved confidence in understanding and speaking in English as a result of the sojourn. However, it transpires that the immersion providers used traditional proficiency focused language assessment tools on entry and exit to measure communication outcomes across the skills of listening, speaking, reading and writing. It appears therefore, that there is a gap between what the perceived outcomes and value are of the Immersion experience, and how they are currently measured. This article reports on a small scale study exploring the perceptions of two immersion providers in Australia, one immersion coordinator in Hong Kong and four returnees on the language assessments they used and experienced, particularly probing on how well they felt these assessments measured their communication gains as a result of the immersion experience.Keywords: Language assessment, immersion, indigenous criteria.